If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -6 = 8 + 6x Reorder the terms: -6 + 12x = 8 + 6x Solving -6 + 12x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 12x + -6x = 8 + 6x + -6x Combine like terms: 12x + -6x = 6x -6 + 6x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + 6x = 8 + 0 -6 + 6x = 8 Add '6' to each side of the equation. -6 + 6 + 6x = 8 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 8 + 6 6x = 8 + 6 Combine like terms: 8 + 6 = 14 6x = 14 Divide each side by '6'. x = 2.333333333 Simplifying x = 2.333333333
| -r+2=20+5r | | 6v+8=-4-v | | 40a+56b= | | w^2-12w+17=0 | | 3(2g-5)=4g+13 | | r^2-5r^2+r=0 | | x+(x+12)=84 | | x-(x*.10)=12000 | | 12x-6=9y | | -t+10=-50+5t | | -t+19=-50+5t | | 8x-3=87-x | | 0.5t=-65 | | x+(x*.10)=12000 | | -5x=4 | | x*.10=12000 | | (3x+2y)(5x-4y)=0 | | -80+14x=-100-6x | | -93-9x=121-31x | | 360=x+35+90+90 | | 7x-9=x+39 | | G=3H+4K | | 7x-18+3x=17 | | 7x-110=2x-10 | | 65-3m=4m-5 | | 2x^2+20x-120=0 | | 107-7x=29x-19 | | -3(3p+6)-2(4-8p)-3(4+2p)=0 | | 15r-5=-10-10 | | 6x^2-48x=9 | | 5x+3+3y=18 | | x+10=-32+19 |